2008
DOI: 10.1177/039463200802100211
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study on Children with Initial Diagnosis of Transient Hypogammaglobulinemia of Infancy: Results from the Italian Primary Immunodeficiency Network

Abstract: Transient hypogammaglobulinemia of infancy (THI) is a heterogeneous disorder characterized by reduced serum IgG levels in early infancy. A putative diagnosis is initially made after exclusion of other causes of hypogammaglobulinemia while a definitive diagnosis of THI can only be made a posteriori in patients with normalization of IgG levels. The aim of this study is to characterize clinical and immunological features of children with an initial diagnosis of THI in correlation to natural outcome, and to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
86
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(91 citation statements)
references
References 25 publications
4
86
0
1
Order By: Relevance
“…In agreement with the literature (13,(15)(16), the main clinical feature in patients with THI were respiratory infections; however, all children had a benign clinical course. Five patients underwent IVIG because they had severe clinical symptoms in winter, a period of high morbidity.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with the literature (13,(15)(16), the main clinical feature in patients with THI were respiratory infections; however, all children had a benign clinical course. Five patients underwent IVIG because they had severe clinical symptoms in winter, a period of high morbidity.…”
Section: Discussionsupporting
confidence: 91%
“…It is important to discriminate between infants who are likely to have early resolution of hypogammaglobulinemia and infants who are likely to have persistence because there is evidence that infants with prolonged unresolved hypogammaglobulinemia are more likely to have recurrent infection and autoimmune problems. [7] This study confirms an easily understood hypothesis: infants with mild or moderate decreases in initial aggregate immunoglobulin levels or IgG levels alone are more likely to outgrow their immunologic deficiency and to do so sooner when compared to infants with greater decreases in immunoglobulin levels. Not surprisingly, infants with higher initial aggregate immunoglobulin levels have a greater probability of prompt resolution.…”
Section: Discussionsupporting
confidence: 83%
“…[6] Without question, some Infants with hypogammaglobulinemia will not have resolution of their deficiency and those infants with persistent hypogammaglobulinemia may be at increased risk for recurrent infection and autoimmune disease. [7] At the time of initial recognition of hypogammaglobulinemia in an infant, since this may be physiologic, immunologists are often finding with clinically relevant questions regarding the likely duration of hypogammaglobulinemia. Previous studies have shown that males are more likely than females to have resolution of hypogammaglobulinemia during infancy, [8] however, other than this observation, there has been little information that would allow an informed prediction about the probable time to resolution to hypogammaglobulinemia.…”
Section: Introductionmentioning
confidence: 99%
“…Bu olgularda, serum IgG düzeyi yaşa göre ortalamanın 2 standart sapma değerinin altındadır. Daha sonra Ig düzeyleri yükselir ve genelde yaşamın 30.-40. aylarında normal değere ulaşır (3,7) . Bazı olgularda bu süre 6 yaşına kadar da uzayabilir (6) .…”
Section: Introductionunclassified